2020
DOI: 10.1007/s40121-020-00296-4
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Viral Suppression, Viral Rebound and State-Specific Duration of HIV Patients with CD4 Count Adjustment: Parametric Multistate Frailty Model Approach

Abstract: Introduction: Combination antiretroviral therapy has become the standard care of human immunodeficiency virus (HIV)-infected patients and has further led to a dramatically decreased progression probability to acquired immune deficiency syndrome (AIDS) for patients under such a therapy. However, responses of the patients to this therapy have recorded heterogeneous complexity and high dynamism. In this paper, we simultaneously model long-term viral suppression, viral rebound, and statespecific duration of HIV-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Our study nding is in harmony with a study by Maina et al [11], who reported that being diagnosed at WHO stage II is associated with higher viral rebound [11]. These ndings suggests that patients at WHO stage II and above have downregulated immune system with associated opportunistic infections and comorbidities, increasing their venerability to viral rebound [39]. Notably, we observed that poor adherence was associated with higher viral rebound.…”
Section: Discussionsupporting
confidence: 91%
“…Our study nding is in harmony with a study by Maina et al [11], who reported that being diagnosed at WHO stage II is associated with higher viral rebound [11]. These ndings suggests that patients at WHO stage II and above have downregulated immune system with associated opportunistic infections and comorbidities, increasing their venerability to viral rebound [39]. Notably, we observed that poor adherence was associated with higher viral rebound.…”
Section: Discussionsupporting
confidence: 91%
“…Based on this, a frail elderly has a higher predisposition to suffer both age-related disorders and non-age-dependent diseases (17). Among these latter, it has been reported that frailty is a powerful predictor of the vulnerability to HIV infection (18)(19)(20) and the lack of an adequate response to retroviral therapy (21). Further studies are necessary to use the frailty as a predictor of the outcome of other viral diseases.…”
Section: The Host: Importance Of the Risk Groupsmentioning
confidence: 99%
“…In this study, patients who seroconverted during the HIV uninfected stage of CAPRISA 002 and other CAPRISA 004 and 008 trials [19,20], were enrolled into the acute HIV Infection phase, and then followed-up during chronic infection and on cART. Further information about these ongoing prospective HIV cohort studies, including women's eligibility criteria, were reported in [18,21,22]. Finally, two hundred and nineteen (219) participants were included in the study.…”
Section: Study Populationmentioning
confidence: 99%
“…The prognostic factors include (1) cART initiation, (2) demographics: age, marital status, educational level, and sex under the influence of alcohol; (3) OI: hypertension and tuberculosis; (4) clinical parameters: WBC components (neutrophils, lymphocyte count, monocytes, eosinophils count, and leucocyte count), Blood chemistry (sodium, chloride, calcium, ALT, AST, total protein and LDH), RBC parameters (Hb, RDW, MCH, MCV, MCHC, and hematocrit) (5) QoL domain scores. Detailed information about the above-mentioned covariates was given in [21,22,24].…”
Section: Variables and Measurementsmentioning
confidence: 99%